A case of testicular tuberculosis mimicking malignancy in a healthy young man. (June 2016) - Abraham, Sherly; Izaguirre Anariba, Dora Ernestina; Dua, Kirandeep; Mir, Mohammad; Ankireddypalli, Arvind
Genitourinary tuberculosis represents a form of extra-pulmonary tuberculosis that occurs in the kidneys, ureters, seminal vesicles, prostate, testis, vas deferens, and epididymis. Isolated testicular involvement is unusual, and differential diagnosis includes testicular tumor, acute infection, infarction, and granulomatous infection. We report a case of a 36-year-old Ecuadorian man residing in New York, New York, who presented with a painful scrotal mass, weight loss, and purulent discharge from ulcerated lesion in scrotal area 10 years following his immigration to the United States. No other systemic symptoms were noted. Positive QuantiFERON-TB Gold and radio imaging results led to the diagnosis. After extensive workup, acid fast bacilli positive cultures obtained by computed tomography guided fine needle aspiration grew Mycobacterium tuberculosis complex. Anti-tuberculosis chemotherapy was initiated after sensitivity tests were confirmed. Significant recovery after 3 months of directly observed therapy was accomplished.